All Days 1992
DOI: 10.2118/24901-ms
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crossflow on Sweep Efficiency in Water/Oil Displacements in Heterogeneous Reservoirs

Abstract: Fluid crossflow can significantly affect sweep efficiency in heterogeneous reservoirs. The importance of fluid crossflow relative to purely longitudinal convective transport in a twodimensional setting depends on several factors. Rock properties such as porosity, permeability, the ratio of vertical to horizontal permeability, and length scale of correlation are important factors. Fluid properties such as phase densities, phase viscosities, and interfacial tension are also factors. Coupled rock-fluid properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…For mobilities greater than 1.0, capillary cross-flow is less important than the viscous cross-flow. Fitzmorris et al, 1992, reached similar conclusions based on a model using several Pc curves and only one Kr data-set. Their results showed that capillary cross-flow was favorable for a water-wet system while unfavorable for an oil-wet one.…”
Section: Introductionsupporting
confidence: 66%
“…For mobilities greater than 1.0, capillary cross-flow is less important than the viscous cross-flow. Fitzmorris et al, 1992, reached similar conclusions based on a model using several Pc curves and only one Kr data-set. Their results showed that capillary cross-flow was favorable for a water-wet system while unfavorable for an oil-wet one.…”
Section: Introductionsupporting
confidence: 66%
“…For such reservoirs, one of the important factors that affects sweep efficiency is cross-flow from one layer into another layer in the direction perpendicular to the main flow path (Fitzmorris et al, 1992). One possible remedy for cross-flow control is simultaneous injection of fluids with different properties (Rossen et al, 2006;Stone, 2004;Surgchev et al, 1996).…”
Section: Introductionmentioning
confidence: 99%